2018
DOI: 10.1002/14651858.cd007858.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Blood pressure-lowering treatment for preventing recurrent stroke, major vascular events, and dementia in patients with a history of stroke or transient ischaemic attack

Abstract: Blood pressure-lowering treatment for preventing recurrent stroke, major vascular events, and dementia in patients with a history of stroke or transient ischaemic attack.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
73
0
7

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(82 citation statements)
references
References 56 publications
2
73
0
7
Order By: Relevance
“…7 In primary prevention, the Systolic Blood Pressure Intervention Trial (SPRINT) 11 proved the benefit of aggressive BP control, demonstrating that targeting a systolic BP less than 120 mm Hg resulted in lower rates of major cardiovascular events compared with less than 140 mm Hg. Although a pooled analysis of 3 studies [12][13][14] (3632 participants) comparing different systolic BP targets suggested that intensive BP lowering reduced the rate of recurrent stroke, no clinical trials to date have tested the effect of such aggressive BP lowering for secondary stroke prevention. In the Recurrent Stroke Prevention Clinical Outcome (RESPECT) Study, we herein tested the hypothesis that targeting intensive BP lowering of systolic and diastolic blood BP less than 120 mm Hg and less than 80 mm Hg, respectively, reduces the rate of stroke recurrence compared with a standard BP-lowering regimen.…”
mentioning
confidence: 99%
“…7 In primary prevention, the Systolic Blood Pressure Intervention Trial (SPRINT) 11 proved the benefit of aggressive BP control, demonstrating that targeting a systolic BP less than 120 mm Hg resulted in lower rates of major cardiovascular events compared with less than 140 mm Hg. Although a pooled analysis of 3 studies [12][13][14] (3632 participants) comparing different systolic BP targets suggested that intensive BP lowering reduced the rate of recurrent stroke, no clinical trials to date have tested the effect of such aggressive BP lowering for secondary stroke prevention. In the Recurrent Stroke Prevention Clinical Outcome (RESPECT) Study, we herein tested the hypothesis that targeting intensive BP lowering of systolic and diastolic blood BP less than 120 mm Hg and less than 80 mm Hg, respectively, reduces the rate of stroke recurrence compared with a standard BP-lowering regimen.…”
mentioning
confidence: 99%
“…Prevention of stroke recurrence following initial stroke or transient ischaemic attack (TIA) is an important focus for secondary prevention, the risk being substantially reduced by good blood pressure (BP) control [1][2][3]. Usual care following stroke and TIA therefore includes regular BP checks and monitoring of anti-hypertensive medications, which are usually carried out in primary care.…”
Section: Introductionmentioning
confidence: 99%
“…В 2018 г. в Кокрановской базе данных T. Zonneveld и соавт. [11] опубликовали крупный обзор по проблеме снижения АД для предотвращения рецидивов инсульта, крупных сосудистых событий и деменции у пациентов с инсультом или ТИА в анамнезе. Целью данного обзора стало изучение эффективности антигипертензивных препаратов, прием которых начат по меньшей мере через 48 ч после постановки диагноза инсульта, для профилактики повторного инсульта, больших ССС и деменции у пациентов с инсультом или ТИА в анамнезе.…”
unclassified
“…Авторы этого крупного Кокрановского обзора [11] на основании полученных данных сделали заключение, что полученные результаты не позволяют сделать выводы относительно оптимального целевого уровня САД у пациентов с перенесенным инсультом или ТИА в анамнезе.…”
unclassified